A comparison of elaborated and restricted feedback in LogEx, a tool for teaching rewriting logical formulae. (21st June 2019) - Lodder, Josje; Heeren, Bastiaan; Jeuring, Johan
Abstract: This article describes an experiment with LogEx, an e‐learning environment that supports students in learning how to prove the equivalence between two logical formulae, using standard equivalences such as DeMorgan. In the experiment, we compare two groups of students. The first group uses the complete learning environment, including hints, next steps, worked solutions, and informative timely feedback. The second group uses a version of the environment without hints or next steps, but with worked solutions, and delayed flag feedback. We use pretest and posttest to measure the performance of both groups with respect to error rate and completion of the exercises. We analyse the loggings of the student activities in the learning environment to compare its use by the different groups. Both groups score significantly better on the posttest than on the pretest. We did not find significant differences between the groups in the posttest, although the group using the full learning environment performed slightly better than the other group. In the examination, which took place 5 weeks after the experiment, the group of students who used the complete learning environment scored significantly better than a control group of students who did not participate in the experiment. Lay Description: What is already known about this topic: An intelligent tutoring system can be very effective in supporting students solving stepwise exercises. Balancing the giving and withholding of feedback in an intelligent tutor can benefit the learning of students. The question, how to decide in general which information should be given at any moment, is a fundamental open problem. What this paper adds: Practicing with the logic tutor LogEx improves skills in propositional logic. There is no significant difference in posttest performance after restricted or elaborated feedback. The examination results of students who received elaborated feedback using LogEx are significantly better than the results of students who did not participate, even after correcting for possible general difference in skills or motivation. Implications of study findings for practitioners: Practicing with an e‐learning tool can help students in learning logic. Providing immediate feedback together with hints and feedback can help students to complete the exercises and improve their performance.